Kebiasaan konsumsi kopi teratur dan pengaruhnya terhadap resorpsi tulang: C-telopeptida dan kalsium serum pada olahragawan - Yusni, Yusni; Rahman, Safrizal (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Coffee is believed and predicted as one of the risk factors for osteoporosis in sedentary and athletes. Long term regular consumption of coffee can lead to hypocalcemia, increase bone resorption and risk of osteoporosis.Objectives: The aim of the study was to analyze the effect of regular coffee consumption on bone resorption, thus predicting the risk of osteoporosis in athletes. The assessment risk of osteoporosis was done by measuring the biomarkers of bone resorption, namely: C-telopeptide (CTx) and serum calcium levels.Methods: The design of this study was a cross-sectional study. The subjects were athletes with regular exercise (aerobic exercise 2 times a week, for 50-60 minutes each training session). The total of samples were 50 people (male = 37; non-coffee=21 and coffee=16 and female=13; non-coffee=7 and coffee=6). Non-coffee is a group that does not consume coffee. Coffee drinkers are a group who regularly consume coffee daily at a dose of 1-2 cups per day (150-200 ml / cup). Coffee consumption habits were obtained from questionnaire interviews. The sampling technique was a total sampling. Examination of serum CTx levels was carried out by the Electro Chemiluminescence Assay method and serum calcium levels were examined using the O-cresolphthalein complexone method. Data were analyzed using the normality test (Kolmogorov-Smirnov), homogeneity (Levene's test) and independent sample t-test, with a significant degree of 95% (p<0.05).Results: The results showed that there was no difference between CTx in male and also female non-coffee (0.415 ng/mL vs. 0.586 ng/mL; p=0.09) and coffee drinkers (0.380 ng/mL vs. 0.512 ng/mL; p=0.35). The normal CTx level is 0.016-0.584 ng/mL. Calcium levels in male (9.70 mg/dL vs. 9.30 mg/dL; p=0.61) and female (9.28 mg/dL vs. 9.23 mg/dL; p=0.72) non-coffee and coffee drinkers were not significantly different. The normal Calcium levels is 9.2-11.0 mg/dL.Conclusion: Regular consumption of coffee does not cause increased CTx and decreased calcium in athletes. Coffee does not cause increased bone resorption, triggers hypocalcemia, therefore regular coffee consumption in physiological doses (1-2 cups/day) is not at risk for early osteoporosis in young athletes.